MODELING AND REVIEW ON ELECTROCHEMICAL DISCHARGE MACHINING - Kumar Pandey, Sandeep; Gehlot, Dilip; Singh, Surbhi; Kharadi, Lokesh (International Journal of Computer Sciences and Engineering, 2025)
Electrochemical discharge machining (ECDM) process utilizes the spark discharge produced by gas film formation during electrolysis. In the conventional ECDM process, precise control of the spark generation is difficult because of the randomness of gas film formation which results in the significant deterioration of process qualities such as excessive overcut, poor machining accuracy and low machining repeatability. The undesirable overcut phenomenon strictly hinders the dimensional miniaturization of CDM process especially when the diameter of the applied tool is much smaller than 100 ptm. In this study a side insulated tool and dilute electrolyte concentration is proposed to reduce the undesirable overcut and thus, to improve the machining resolution of the ECDM process. Experiments are conducted with various machining parameters, such as spark ignition voltage, electrolyte concentration, and tool insulation. As a result, the feasibility of miniaturization in the ECDM process is phenomena. successfully improved by reducing the excessive overcut